Microbial Diversity in a North Western Mediterranean Sea Shallow Coastal Lagoon Under Contrasting Water Temperature Conditions - Trombetta, Thomas; Bouget, François-Yves; Félix, Christine; Mostajir, Behzad; Vidussi, Francesca (Frontiers in Marine Science, 2022)
Temperature and light mainly drive seasonal dynamics of microbial planktonic diversity in coastal ecosystems; however, disentangling their effects is challenging because they are always tightly coupled. Shallow coastal lagoons exhibit intense temperature changes throughout the year and high interannual temperature fluctuations, offering the opportunity to study temperature effects on microbial community diversity and succession. Weekly sampling at 16s and 18s rRNA gene OTU diversity associated with high-frequency meteorological and hydrological monitoring was conducted in the northwestern Mediterranean Thau Lagoon (South of France) from winter to spring in 2015 and 2016. While 2015 was a normal climatic year, 2016 had the warmest winter ever recorded in southern France. Water temperature was found to be the main driver of community diversity and succession from winter to spring. During the normal temperature year of 2015, bacterial communities were dominated by Proteobacteria and Bacteroidetes, archaeal community by Thaumarachaeota, and unicellular eukaryotes mainly by picochlorophytes (Bathycoccus prasinos, Micromonas bravo, and Ostreococcus spp.) in winter and diatoms (Chaetoceros spp.) in spring. The unusually warm year 2016 benefited Actinobacteria (ML602J-51), Cyanobacteria (Synechococcus), the picoeukaryote Ostreococcus spp., and several dinoflagellates. Our results suggest that in a warmer ocean, smaller organisms will dominate microbial communities in shallow coastal waters, potentially affecting ecosystem services.